Definition of trAnscatheter heart Valve orIeNtation in biCuspId aortic valve: The DA VINCI pilot study - Tarantini, Giuseppe; Fabris, Tommaso; Nai Fovino, Luca; Cardaioli, Francesco; Pergola, Valeria; Montonati, Carolina; Rodinò, Giulio; Cabrelle, Giulio; Massussi, Mauro; Scotti, Andrea; Zuccarelli, Vittorio; Sciarretta, Tommaso; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives To assess the impact of conventional transcatheter heart valve (THV) commissural alignment techniques on THV/coronary overlap and coronary access (CA) after transcatheter aortic valve replacement (TAVR) in bicuspid aortic valve (BAV). Background Specific Evolut Pro/Pro + and Acurate Neo2 THV orientations are associated with reduced neo-commissural overlap with coronary ostia in tricuspid aortic anatomy. Whether standard orientation techniques are effective also in the setting of BAV anatomy has not been studied. Methods The DA VINCI (Definition of trAnscatheter aortic Valve orIeNtation in biCuspId aortic valve) pilot study is a prospective registry enrolling consecutive patients with severe BAV stenosis undergoing TAVR with last generation supra-annular tall-frame THVs implanted with a cusp overlap view-based commissural alignment. Patients underwent pre- and post-TAVR computed tomography (CT) and coronary angiography. The study endpoint was the rate of favorable THV/coronary overlap, defined as an angle > 40° between the THV commissural post and coronary ostia. Other endpoints were the rates of successful THV alignment with respect to the raphe and of selective CA after TAVR. Moreover, different virtual THV alignment models were tested to identify which one would produce the lower degree of THV/coronary overlap. Results Thirty-four patients with type 1 BAV with right-left raphe undergoing TAVR (23 with Evolut Pro/Pro + and 11 with Acurate Neo2) were included. At pre-TAVR CT, moderate/severe cusp asymmetry was found in 50% of patients, severe coronary ostia eccentricity was observed in 47.1% for the RCA vs. 8.8% for the LCA (P < 0.007). Correct TVH orientation was achieved in 29 cases. At post-TAVR CT, optimal THV alignment/mild misalignment to the raphe was observed in 86.2%, but a moderate/severe overlap with the coronaries was seen in 13.7% for the RCA and 44.8% for the LCA (P = 0.019). After TAVR, selective RCA cannulation was possible in 82.8% vs. 75.9% for the LCA (P = 0.74), while combined selective CA of both coronaries was possible in less than two-thirds of the patients. Virtual THV alignment in the coronary ostia overlap view assuming a hypothetical circular THV expansion would produce an optimal THV/coronary overlap in almost 90% of cases. Conclusion Given cusp asymmetry and coronary ostia eccentricity of BAV combined with potential THV asymmetrical expansion, conventional commissural alignment techniques are associated with higher rates of THV misalignment and of moderate/severe neo-commissure overlap with the coronary ostia as compared to tricuspid aortic stenosis, resulting in lower rates of selective CA after TAVR. A modified THV orientation technique based on the coronary ostia overlap view might be preferable in BAV patients.